PERAN PENDIDIKAN KRISTEN DALAM MEMBENTUK KARAKTER DAN NILAI SPIRITUAL DI ERA MODERN - Sari Arselia; Yespin siang, Yelpianti Barrang, Yelia Sampe, Alfrets Obaja (ADISAM PUBLISHER, 2025)
Christian education has an important role in shaping the character and spiritual values of students, especially in the modern era which is full of moral and ethical challenges. This article discusses how Christian education, through a holistic approach that combines academic, moral and spiritual aspects, can form individuals who have integrity, are based on faith and have social concern. With learning methods based on Bible values, Christian education does not only focus on intellectual achievement but also on strengthening faith and developing character in accordance with the teachings of Christ. The challenges of globalization, secularization and technological developments are a test for Christian education in maintaining its relevance amidst changing times. This article highlights strategies that can be implemented by Christian educational institutions to remain effective agents of transformation in forming a generation that is not only academically intelligent but also firm in faith and morality